2006
DOI: 10.7124/bc.00072a
|View full text |Cite
|
Sign up to set email alerts
|

The indoline alkaloids accumulation by Rauwolfia serpentina cell lines upon surface and submerged maintenance

Abstract: The indoline al ka loids ac cu mu la tion by R. serpentina cell lines upon sur face and sub merged main te nanceThe In sti tute of Mo lec u lar Bi ol ogy and Ge net ics, NAS of Ukraine 150, Ac a de mi cian Zabolotny Str., Kyiv, 03143, Ukraine kunakh@imbg.org.ua Indoline al ka loids ac cu mu la tion, in clud ing ajmaline, in the bio mass of R. serpentina cell line cul ture on the ex am ple of hor mone in de pend ent highly pro duc tive strain K 27 at its sur face and sub merged main te nance in nu tri ent me di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The genealogy of the К-27 strain of R. serpentina, the details of its establishment and culturing along with the characteristics and peculiarities were reported earlier [3,[7][8][9]. Over more than 35 years, this strain was stable in terms of both productivity, genetic and cytological characteristics, being grown on both liquid and solid media of various composition with or without different organic additives [16,17,26,[18][19][20][21][22][23][24][25].…”
Section: Molecular and Cell Biotechnologiesmentioning
confidence: 79%
See 2 more Smart Citations
“…The genealogy of the К-27 strain of R. serpentina, the details of its establishment and culturing along with the characteristics and peculiarities were reported earlier [3,[7][8][9]. Over more than 35 years, this strain was stable in terms of both productivity, genetic and cytological characteristics, being grown on both liquid and solid media of various composition with or without different organic additives [16,17,26,[18][19][20][21][22][23][24][25].…”
Section: Molecular and Cell Biotechnologiesmentioning
confidence: 79%
“…We have previously shown that the amount of DNA in cultured cells increases during a subculture cycle when they switch to alkaloid biosynthesis [29]. Obviously, in mixoploid cell populations of R. serpentina culture in vitro, there may be a dependence of strain productivity, in particular indoline alkaloid biosynthesis, on the ploidy of cells that formed the modal class [30]. However, other researchers found a negative correlation between the chromosome number and the accumulation of secondary metabolites in cultured R. serpentina cells [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a study of the build-up of indole alkaloids and the overall productivity of the K-27 strain when grown under different conditions (surface and submerged cultivation) on different types of nutrient media have been published previously [5,6]. It was shown that accelerated buildup of alkaloids occurs under specially selected conditions of submerged cultivation; this, in turn, makes it possible to reduce the time needed to culture the tissues prior to harvesting.…”
Section: Introductionmentioning
confidence: 99%